How Artificial Intelligence Helps SMEs Make Better Decisions under Sudden Global Shocks: A Resilience Path from Sensing to Simulation, Optimization, and Continuous Correction - Lin, Yuchang (Computers and Artificial Intelligence, 2026)
This essay examines how artificial intelligence (AI) can improve the decision quality and resilience of small and medium-sized enterprises (SMEs) during sudden global shocks, including tariff changes, sanctions, logistics disruptions, exchange-rate volatility, and compliance rule shifts. It argues that the primary value of AI for SMEs is not perfect prediction, but the creation of a resilience-oriented decision system that helps firms respond faster and more systematically under uncertainty. The paper proposes a four-stage decision chain—risk sensing, scenario simulation, constrained optimization, and continuous monitoring/correction—to explain how AI can support SMEs in detecting credible signals, comparing alternative actions, allocating limited resources under real constraints, and adapting decisions as conditions change. The analysis further applies this framework to three high-impact SME contexts: supply-chain disruption, pricing and foreign-exchange shocks, and cross-border compliance volatility. In addition, the essay outlines a practical implementation roadmap for SMEs that emphasizes incremental adoption, minimal data governance, workflow integration, and trigger-based decision rules. Finally, it discusses major risks and limitations, including poor data quality, structural breaks, generative AI hallucinations, privacy and cross-border data governance concerns, and weak organizational accountability. The essay concludes that AI can materially strengthen SME resilience when deployed as a governed, human-supervised decision chain rather than a one-time predictive tool.